2017
DOI: 10.4196/kjpp.2017.21.1.133
|View full text |Cite
|
Sign up to set email alerts
|

Calcium permeability of transient receptor potential canonical (TRPC) 4 channels measured by TRPC4-GCaMP6s

Abstract: Conflicting evidence has been obtained regarding whether transient receptor potential cation channels (TRPC) are store-operated channels (SOCs) or receptor-operated channels (ROCs). Moreover, the Ca/Na permeability ratio differs depending on whether the current-voltage (I-V) curve has a doubly rectifying shape or inward rectifying shape. To investigate the calcium permeability of TRPC4 channels, we attached GCaMP6s to TRPC4 and simultaneously measured the current and calcium signals. A TRPC4 specific activator… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 39 publications
0
11
0
Order By: Relevance
“…The study also uncovered that the application of EA on TRPC4 or 5-overexpressed human embryonic kidney (HEK) cells activates the channels and induces cell death in consequence of increasing intracellular calcium levels [9]. Such results were supported by our previous studies where we reported Gα i , oxidized glutathione and constitutively active mutant of TRPC4, 5 increased intracellular Ca 2+ [3610] and used TRPC4-GCaMP6 to find that EA increased calcium levels near TRPC4 channels [11]. However, the mechanism of EA-induced activation of the ion channels is unclear.…”
Section: Introductionmentioning
confidence: 64%
See 1 more Smart Citation
“…The study also uncovered that the application of EA on TRPC4 or 5-overexpressed human embryonic kidney (HEK) cells activates the channels and induces cell death in consequence of increasing intracellular calcium levels [9]. Such results were supported by our previous studies where we reported Gα i , oxidized glutathione and constitutively active mutant of TRPC4, 5 increased intracellular Ca 2+ [3610] and used TRPC4-GCaMP6 to find that EA increased calcium levels near TRPC4 channels [11]. However, the mechanism of EA-induced activation of the ion channels is unclear.…”
Section: Introductionmentioning
confidence: 64%
“…4). We also showed that TRPC4 was activated by EA [11]. In addition, EA activated TRPC1/4 and TRPC1/5 heteromer and induced cell toxicity via Na + influx instead of Ca 2+ influx [1819].…”
Section: Discussionmentioning
confidence: 99%
“…However, Trpc3 Ca 2+ permeability exceeds that of monovalent cations, i.e., P Ca /P Na > 1 [14,16,46,63], which is inconsistent with a current like I CAN that is selective for monovalent cations yet gated by Ca 2+ . Nevertheless, heteromeric Trpc channels that include Trpc1 diminish Ca 2+ permeability such that P Ca /P Na < 1 [30,64,65]. Trpc3 can form heteromeric channels with Trpc1 [6568] as well as Trpc6 and Trpc7 [68,69].…”
Section: Discussionmentioning
confidence: 99%
“…The calcium permeability of TRPC4 and TRPC5 channels is changed when TRPC1 subunits are co-expressed with them 9 . We also have recently proposed that heteromerization of TRPC4 with TRPC1 decreased the calcium rise as detected by channels tagged with GCaMP6s 36 . Here, our data showed that estimated functional PI(4,5)P 2 dissociation curves of TRPC1/4, TRPC1/5 heteromeric channels are not very different, which means that introducing TRPC1 subunits normalizes their PI(4,5)P 2 sensitivities.…”
Section: Discussionmentioning
confidence: 92%